When the earth shakes : earthquakes, volcanoes, and tsunamis - Winchester, Simon (Viking, 2015)
"'New York Times' bestselling author, explorer, journalist, and geologist Simon Winchester who's been shaken by earthquakes in New Zealand, skied through Greenland to help prove the theory of plate tectonics, and even charred the soles of his boots climbing a volcano looks at the science, technology, and societal impact of these inter-connected natural phenomena"--